Pengaruh Permainan Tradisional Sunda “Galah Asin” Untuk Meningkatkan Keterampilan Kolaboratif Siswa Di Madrasah Ibtidaiyah Nagarakasih 2 Tasikmalaya - Metha Irmawayani; Laili Rahmatul Fajri (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2020)
This study aims to find out the influence of sundanese traditional games named “galah asin” to increase collaborative skill of elementary school student at madrasah ibtidaiyah Nagarakasih 2 Tasikmalaya City. This study involved elementary school students for its subjects. Subject in this study were students of Madrasah Ibtidaiyah 2 Nagarakasih. Researcher of this study uses an experimental method, with a pretest – posttest control group design. Experimental methode uses a treatment implementation to experimental group. The treatment in this study consist of a series of “galah asin” games. The instrument used to measure collaborative skill was developed from the theory of Trilling and Fadel (2009). This study uses Paired sample T-test for it’s methods of data analysis. This methods help out this study to find out a presence or an absence of the differences collaborative skill score between experimental group and control group, also the differences collaborative skill score between before and after treatment implementation. The results showed that Sig (2-tailed) 0.000, score < 0.05. It means that traditional games named “galah asin have an influences to increase student collaborative skill. Beside that, that research also find pretest collaborative skill score of the experimental group is 2208, while the amount of the posttest collaborative skill score of the experimental group is 3035. There is a difference (gain score) of 827, traditional games named “galah asin can increase collaborative skill for 37,5%.